COMPETENCY APPROACHES IN THE PREPARATION OF CHILDREN FOR SCHOOL EDUCATION IN THE PRESCHOOL ORGANIZATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Today, it provides for a compensatory approach to achieving the quality and effectiveness of preschool education, enriching the groups with relevant literature for each age group, organizing the daily activities of children meaningful and interesting, using their free time efficiently, identifying their abilities and, accordingly, a creative approach to the process, conducting a rational and systematic analysis of the lessons and resources. In this article discusses information about competency approaches in the preparation of children for school education in the preschool organization.